The use of intersentence relational particles and asyndeton in First Peter - Janse, Van Rensburg J. J. (1990)
This paper's discussion utilises the classification of meaningful relations between internuclear structures proposed by Nida, Louw, Snyman and Cronje in their book 'Style and discourse'; with special reference to the text of the Greek New Testamentand also the information in Domain 89 (Relations) of the Louw-Nida Lexicon, and Domain 91 (Discourse Markers).
Keywords: Subordinate; Paratactic conjunctions; Macro-structure of the letter; Logical; linguistic theory; Hypotactic conjunctions; Grammatical closure; Forward-pointing pronoun; Exegetical section; Equivalent; Demonstrative adverb; Coordinate; Causa1 co-ordinating conjunctions; 'Zero' morpheme; Asyndeton